IMPROVEMENT IN ACCURACY AND COMPUTATION TIME FOR ELASTIC FINITE DIFFERENCE MODELLING. - CHIN , TEE ANG (2019)
In hydrocarbon exploration, seismic reflection imaging is used to image the subsurface. However, in complex areas such as shallow gas overburden, highly faulted zone, coal or pre-salt/pre-carbonate, the imaging of these areas appears to be challenging. Gas wipe out, or gas masking in particularly, is a very common issue in Malaysia, where more than 45% of Malaysian fields is suffering from gas clouds masking. This indirectly caused millions of barrels of oil remained undiscovered due to poor imaging.